ANALYSIS OF OVERHEAT OF PERTAMAX FUEL DISTRIBUTION PUMP FOR MAINTENANCE ACTION AT PT. PERTAMINA PATRA NIAGA–FUEL TERMINAL MEDAN GROUP - Mukhnizar , Mukhnizar; Risal Abu; Fauzan Rinaldi (Ikatan Dosen Menulis, 2024)
This study aims to analyze the causes of overheating in Pertamax fuel pumps at PT. Pertamina Patra Niaga–Fuel Terminal Medan Group and determine the appropriate maintenance actions to prevent operational failures. Overheating in pumps can cause serious damage and operational disruptions that have the potential to disrupt fuel distribution. The methodology used includes collecting operational data, analyzing pump conditions using infrared thermography, and evaluating pump performance based on industry standards. The results of the study indicate that overheating is caused by several factors such as component wear, inadequate lubrication, and fluid flow instability. Based on these findings, several preventive and predictive maintenance actions are recommended, including maintenance rescheduling, improving the lubrication system, and implementing real-time temperature monitoring. The implementation of these maintenance actions is expected to improve pump reliability and reduce the risk of overheating in the future.